Peningkatan Kapasitas Kader Posyandu Melalui Pelatihan Pemantauan Pertumbuhan dan Perkembangan Balita di Wilayah Kerja Puskesmas Kereng Bangkirai Kecamatan Sebangau Palangka Raya - Noordiati Noordiati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Monitoring the development of early childhood is a family task, but not all families can carry out this task optimally. Busyness, lack of knowledge, and the socio-economic condition of the family are factors that do not support this effort. Therefore, monitoring children's growth is coordinated through the role of the community through the Posyandu program. Posyandu, as one of the community-based health efforts, has a vital role in providing convenience to the community in obtaining essential services. To achieve this goal requires the role of a Posyandu cadre who has the knowledge and skills in monitoring child growth and development. The method of activity is carried out by providing material for child development and practicum on how to assess and measure children's growth and development. The results of activities were measured through differences in the results of the pre-test and post-test, as well as the results of observations when cadres provided services during Posyandu implementation. The results of the activity showed that the training in monitoring the growth and development of children under five given to Posyandu cadres could increase the knowledge and skills of cadres in providing services at Posyandu related to monitoring the growth and development of children under five.